2017
DOI: 10.1016/j.devcel.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Framework for the Embryonic Initiation of Shoot Meristem Stem Cells

Abstract: The establishment of pluripotent stem cells is a key event during plant and animal embryogenesis, but the underlying mechanisms remain enigmatic. We show that in the flowering plant Arabidopsis thaliana, expression of the shoot meristem stem cell marker CLV3 becomes detectable in transition stage embryos. Surprisingly, the key regulator of stem cell homeostasis WUSCHEL (WUS) is expressed but dispensable for stem cell initiation. Rather, the WUS paralog WOX2, a regulator of embryo patterning initiated in the zy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 68 publications
6
88
0
Order By: Relevance
“…Reduced levels of the relevant PLT, SCR, and TCP proteins in primary roots and their embryonic progenitors, regenerating roots, and LRPs reveal dose-dependent defects in the specification and activity of organizer cells within the root stem cell niche: the QC cells. Our genetic and protein interaction data indicate that dosage-sensitive combinatorial interactions among PLT-TCP-SCR directly regulate promoter activity of the WOX5 gene, which is the best-studied specific molecular marker for QC activity (Sarkar et al 2007;Pi et al 2015;Zhang et al 2017b). Consistent with this scenario, overexpressed PLTs can only effectively expand the WOX5 expression domain where SCR and TCP also are highly expressed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Reduced levels of the relevant PLT, SCR, and TCP proteins in primary roots and their embryonic progenitors, regenerating roots, and LRPs reveal dose-dependent defects in the specification and activity of organizer cells within the root stem cell niche: the QC cells. Our genetic and protein interaction data indicate that dosage-sensitive combinatorial interactions among PLT-TCP-SCR directly regulate promoter activity of the WOX5 gene, which is the best-studied specific molecular marker for QC activity (Sarkar et al 2007;Pi et al 2015;Zhang et al 2017b). Consistent with this scenario, overexpressed PLTs can only effectively expand the WOX5 expression domain where SCR and TCP also are highly expressed.…”
Section: Discussionmentioning
confidence: 52%
“…During initiation of the embryonic shoot stem cells, a WOX2 module promotes the expression of HD-ZIPIII genes to ensure the appropriate ratio of cytokinin and auxin pathways (Zhang et al 2017b). During de novo shoot regeneration, cytokinin B-type Arabidopsis response regulators (ARRs) combine with HD-ZIP III coactivators for region-specific activation of the WUS promoter (Zhang et al 2017a), whereas, in the SAM, ARRs appear to maintain mainly WUS expression (Meng et al 2017;Zhang et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, defective stem cell homeostasis alone could explain the lack of AM in wus mutants. Recent work on embryonic shoot stem cell initiation indicated that WUS is dispensable for stem cell initiation and that several members of the WUSCHEL-RELATED HOMEOBOX gene family redundantly function in this process in embryos (Zhang et al, 2017). It remains to be tested whether WUS is required for stem cell initiation in the AM, in addition to its role in stem cell homeostasis.…”
Section: Wus Is Required For Am Initiation and Integritymentioning
confidence: 99%
“…LEAFY COTYLEDON1 (LEC1) is a central regulator of seed development, and marks zygotic embryos during normal development (Lotan et al, 1998). WUSCHEL RELATED HOMEOBOX 2 (WOX2) plays a role in initiating shoot meristem stem cells in embryos (Zhang et al, 2017). Its expression starts in the fertilized egg and is localized in the apical half of the embryo after asymmetric cell division (Ueda et al, 2011).…”
Section: Expression Pattern Of Embryonic Markers and Selection Of Se-mentioning
confidence: 99%